1933 Haw. Sess. Laws 38, An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 6 - (:unkn) unknown (General Publisher, 1933)
Prohibited individuals convicted of violent crimes from owning, possessing, or having under their control a pistol, revolver, or ammunition.
--
Keywords: POSSESSION - DANGEROUS PERSONS